2020
DOI: 10.1002/ajmg.c.31793
|View full text |Cite
|
Sign up to set email alerts
|

Integration and reanalysis of transcriptomics and methylomics data derived from blood and testis tissue of men with 47,XXY Klinefelter syndrome indicates the primary involvement of Sertoli cells in the testicular pathogenesis

Abstract: Klinefelter syndrome (KS; 47,XXY) is the most common sex chromosomal anomaly and causes a multitude of symptoms. Often the most noticeable symptom is infertility caused by azoospermia with testicular histology showing hyalinization of tubules, germ cells loss, and Leydig cell hyperplasia. The germ cell loss begins early in life leading to partial hyalinization of the testis at puberty, but the mechanistic drivers behind this remain poorly understood. In this systematic review, we summarize the current knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 121 publications
1
28
0
Order By: Relevance
“…Emerging single-cell RNA-seq (scRNA-seq) methods have enabled the quantitative characterization of cell populations within the testis and can clearly contribute new insights into the pathologic mechanisms of KS. Pioneering scRNA-seq studies of KS have emerged in the past year, hinting at a special role for the Sertoli cell in KS pathology, [17][18][19] but insights have been limited by the small number of donors and suitable analysis tools. An scRNAseq framework is needed to delineate the role of the X chromosome in KS and separate expression changes that are general responses to spermatogenic impairment versus causes of KS-specific pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging single-cell RNA-seq (scRNA-seq) methods have enabled the quantitative characterization of cell populations within the testis and can clearly contribute new insights into the pathologic mechanisms of KS. Pioneering scRNA-seq studies of KS have emerged in the past year, hinting at a special role for the Sertoli cell in KS pathology, [17][18][19] but insights have been limited by the small number of donors and suitable analysis tools. An scRNAseq framework is needed to delineate the role of the X chromosome in KS and separate expression changes that are general responses to spermatogenic impairment versus causes of KS-specific pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Winge et al recently compared all published studies concerning differentially expressed analyses and revealed an overlap of only eight transcripts which were up-regulated in at least two studies on testis tissue, while no down-regulated genes overlapped between the studies 60 . Of these eight genes, only one was found differentially expressed in our analysis of fibrotic versus non-fibrotic tissue, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Next, why is the risk approximately 70-fold increased in males with Klinefelter syndrome (24)? People with sex-chromosome constitution that results in Klinefelter syndrome, usually XXY, have disturbed spermatogonial niches, such that at puberty virtually no germ cells remain (25), and probably also no GCNIS cells are retained. This deficiency would explain why these individuals are infertile and hardly develop testicular type II GCTs.…”
Section: Discussionmentioning
confidence: 99%